Association between caries status and quality of life of adults in Pinrang, 2019 - Rasmidar Samad (DiscoverSys Inc., 2019)
Objective: To analyzeassociation between caries status and quality of life of adult in Pinrang, 2019; promoting epidemiology data in planning and evaluation of oral health care programs. Material and Methods: This study used pilot pathfinder design. The subject compromised of 345 subjects aged ≥ 18 years old and randomly selected from urban and rural areas in Pinrang, Indonesia. The data were collected by 194 subject from urban area and 151 subject from rural areas. We used DMF-T index according to WHO methodology and Oral Health Impact Profile (OHIP-14) questionnaire translated to Bahasa (Indonesia version). Results: Based on gender, DMF-T index of males was lower than females in urban areas, whereas DMF-T index of males was higher than women in rural areas. In urban and rural areas, the mean of F (filled) component was 0.00. The highest DMF-T index was at subjects aged > 60 years, 17.19 in urban areas and 16.52 in rural areas, respectively. There was no significant association between caries status and quality of life both in urban and rural areas in subjects aged 18-44 years old (p > 0.05). As for subjects aged ≥ 45 years in urban areas, it was observed that there was a significant relationship between caries status and the quality of life (p <0.05).Conclusion: There was no significant association between caries status aged 18-44 years and quality of life in urban and rural areas. In adults aged ≥ 45 years, the results showed that there was no significant association between caries status and quality of life of adults in rural areas and a significant association between caries status and the quality of life of adults in urban areas.